6-Bromo-1,3-dimethyl-1H-imidazo[4,5-b]pyridin-2(3H)-one - Dahmani, S.; Rodi, Y.K.; Zouihri, H.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The non-H atoms of the two independent molecules in the asymmetric unit of the title compound, C(8)H(8)BrN(3)O, are planar (r.m.s. deviations = 0.015 and 0.019 A). In the crystal, the molecules are linked into a zigzag chain along the c axis by C-H...O hydrogen bonds.